2015
DOI: 10.1002/cpp.1963
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Detention under the Mental Health Act for Adults with Anorexia Nervosa

Abstract: People detained under the mental health act with anorexia nervosa often respond by engaging in a battle with clinicians. This follows by the person withdrawing into a 'bubble' where the individual starts to feel some relief that they are no longer in control of their eating, but this competes with the lack of self and the emerging anorexic self. Clinicians need to be aware that individuals detained may have mixed feelings about their hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 30 publications
1
44
0
3
Order By: Relevance
“…In common with another study from the UK [9], Chinese participants also reported a culture of restriction, which they described as excessive 'strictness' and perceived the inpatient unit as an alternate reality, similar to the 'bubble' described in Seed et al's [12] UK sample. Haynes et al's [8] sample and the Chinese participants both reported using relational strategies to cope with the 'bubble' of hospitalization, such as being overly compliant and cooperative, secretive behaviors around eating and competing with other experiencing people.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In common with another study from the UK [9], Chinese participants also reported a culture of restriction, which they described as excessive 'strictness' and perceived the inpatient unit as an alternate reality, similar to the 'bubble' described in Seed et al's [12] UK sample. Haynes et al's [8] sample and the Chinese participants both reported using relational strategies to cope with the 'bubble' of hospitalization, such as being overly compliant and cooperative, secretive behaviors around eating and competing with other experiencing people.…”
Section: Discussionsupporting
confidence: 55%
“…Previous work has investigated the lived experiences of this group of individuals requiring hospitalization using qualitative methodologies. Studies from the UK [6][7][8][9][10][11][12][13], The Netherlands [14], Norway [15] and Australia [16] all report themes of control versus collaboration, removal from normality, the negative and positive impacts of peer relationships, transition and recovery, disconnection from the outside world, the role of meals and eating, battling the ED and taking responsibility. In these countries, inpatient treatment tends to involve physical rehabilitation alongside psychotherapies including cognitive behavioral therapy (CBT) and family therapy [17] and individuals may be admitted voluntary or detained and treated using legal frameworks like the UK's Mental Health Act [18].…”
Section: Introductionmentioning
confidence: 99%
“…Motivation to change has also been shown to increase gradually during admission (33). These changes could reflect an improvement in the decision-making capacity found in a third of patients admitted with anorexia nervosa (29) or patients giving up their resistance to treatment (23). Hence, changes in motivation and the perception of admission need have been a crucial argument for persuading patients into admission.…”
Section: Attitude Toward Treatmentmentioning
confidence: 99%
“…Attitude toward treatment is an important topic when discussing the involuntary treatment of anorexia nervosa, as these patients often lack the motivation to change or refuse to accept they have a treatment need (28). Their decision-making capacity and their attitudes toward treatment are affected by the ego syntonic nature of the disease (23,29,30). At the intrapsychic level, Seed et al (23) argue that the self is occupied by the illness and Tan et al (31) describe how patients' value system changes because of anorexia nervosa, resulting in weight-related issues overshadowing other aspects of their life.…”
Section: Attitude Toward Treatmentmentioning
confidence: 99%
See 1 more Smart Citation